1104 Plasma Circulating Cell-Free Messenger RNA as a Potential Biomarker of Melanoma. (12th October 2021) - Ita, M; Wang, J H; Fanning, N; Kaar, G; Lim, C; Redmond, H
Abstract: Introduction: Blood-borne cell-free nucleic acids are increasingly emerging as significant non-invasive adjuncts to current methods of disease status evaluation in cancer patients. In this study, we sought to examine whether significant differences exist in the plasma transcriptomic profile of advanced melanoma patients with a high disease burden compared to patients with therapeutic response. Method: Plasma circulating cell-free messenger ribonucleic acid (ccfmRNA) was extracted from twenty patients with stage IV melanoma receiving immunotherapy. Pathway focused gene expression analysis was performed. Patients were assessed with paired blood sample collection and CT scan assessments at baseline and at 3 months follow up. Response Evaluation Criteria in Solid Tumours (RECIST 1.1) was used for tumour burden estimation. Results: In stage IV melanoma patients, CCL5, GZMB and MYD88 genes were significantly over-expressed (p < 0.05 versus healthy controls). In patients with high disease burden or progressive disease, CCL18, CCR1, CCR4, CD274, CSF2, and GBP1 genes were significantly over-expressed (p < 0.05 versus patients with therapeutic response). Finally, in stage IV melanoma patients with brain metastases, CCL18, CCR1, CCR4, CD274, CSF2, EGF, GBP1, and PTGS2 genes were significantly over-expressed (p < 0.05, versus patients without brain metastasis). Conclusions: Significant differences were observed in the plasma transcriptomic profile between the various melanoma patient groups, and we postulate that these differences may be exploited to identify novel therapeutic targets or biomarkers relevant to melanoma. CCL4 and CCL5 are prognostic in melanoma, both genes had significantly higher expressions in low disease burden patients compared to patients with a high disease burden.